Virulence of Japanese Encephalitis Virus Genotypes I and III, Taiwan - Fan, Yi-Chin (Emerg Infect Dis, 2017)
The virulence of genotype I (GI) Japanese encephalitis virus (JEV) is under debate. We investigated differences in the virulence of GI and GIII JEV by calculating asymptomatic ratios based on serologic studies during GI- and GIII-JEV endemic periods. The results suggested equal virulence of GI and GIII JEV among humans.